Computational Fluid Dynamics (CFD) Simulation of Indoor Air Quality Optimization - Dongari, Sudarshan; Souda, Saveen (Journal of Progress in Civil Engineering, 2025)
Indoor air quality (IAQ) in common vertical circulation spaces has become increasingly important due to rising urbanization and the growing trend of indoor living. Poor IAQ in these shared spaces, where residents frequently move in and out of their apartments, can have a significant impact on occupant well - being, especially during events like the COVID - 19 pandemic. To address this issue, this paper investigates the influence of design parameters on IAQ variables using a simulation - based approach with computational fluid dynamics (CFD). The results show a strong correlation between space design and key IAQ factors, including air changes per hour (ACH), humidity, and CO2 concentration, revealing potential challenges such as inadequate ventilation and increased risk of infection transmission. In response to these findings, the study recommends a re - examination of the design of common vertical circulation spaces in future housing developments and proposes strategies to improve natural ventilation and overall IAQ. The proposed solutions aim to enhance indoor environmental quality and occupant health. This research provides valuable insights into the relationship between space design and IAQ, offering actionable recommendations for improving building design practices in response to modern health and comfort needs.